Marketing Communication Strategy Through Events In Increasing Brand Awareness Sentrum Space: English - Ardhi Mulia Rahmat Wijaya; Sumadi Sumadi (International Journal of Business and Quality Research, 2024)
This research is entitled marketing communication strategies through events in increasing Sentrum Space brand awareness. Researchers conducted research on the marketing team at Sentrum Space. This research aims to identify, surface and assess the impact of implementing marketing communication strategies in growing brand awareness at Sentrum Space. This research was conducted on the basis of the digital marketing phenomenon, especially in terms of marketing communications in the coffee shop industry, which is widely implemented by competitors in the same industry. This research uses a qualitative approach with observation and interview methods with representative units of analysis to provide information and data relevant to the research topic. This research resulted in findings that marketing communication strategies through events can provide significant benefits in increasing Sentrum Space brand awareness by providing a platform to introduce the brand to a wider audience and create awareness of the products or services offered. Strong brand awareness helps differentiate Sentrum Space from competitors, where consumers tend to choose brands they know and trust. Events enable direct interaction with potential customers, building closer and deeper relationships, and reaching wider market segments. However, marketing communications and creativity that were less than optimal meant that its distribution was not widespread. The use of social media Instagram was deemed less effective in helping to carry out the event.